Mapas mentales de la Ciudad de México: una aproximación psicosocial al estudio de las representaciones espaciales - de Alba, Martha (El Colegio de México A.C., 2004)
This study presents the results of a study on mental maps of Mexico City in a sample of residents of the Federal District (DF), with the aim of determining how the metropolitan zone is imagined and experienced by its residents. The mental maps were analyzed qualitatively and quantitatively on the basis of the theory of social representations (Moscovici, 1961), from which they can be conceived as socially elaborated representations of space. The author also provides a conceptual framework and methodology for dealing with spatial images.